Gender-specific reference charts for cardiotocographic parameters throughout normal pregnancy: a retrospective cross-sectional study of 9701 fetuses. (April 2016) - Amorim-Costa, Célia; Cruz, Joana; Ayres-de-Campos, Diogo; Bernardes, João
Abstract: Objective: To establish reference values for cardiotocographic (CTG) parameters from 24 to 41 weeks of gestation in normal pregnancies. Study design: Retrospective cross-sectional study, using the first antepartum tracing of singleton fetuses with normal pregnancy outcomes (term birth, normal birthweight, normal umbilical artery pH and Apgar scores, no intensive care unit admission). Cases were consecutively selected from a hospital electronic patient record, and analyzed using the OmniviewSisPorto 3.7 system. Variables were compared between male and female fetuses, by gestational age, and percentile curves were constructed. Results: A total of 9701 tracings (corresponding to 9701 fetuses) were analyzed. All CTG parameters changed significantly throughout gestation in both genders, with a decrease in baseline and decelerations, and an increase in average long-term variability (LTV), average short-term variability (STV), accelerations and uterine contractions. The mean baseline value decreased 9 bpm, and its range almost doubled from 24 to 40 weeks. Until 30 weeks the lower percentiles for average LTV were below 5 bpm, and the minimum value for average STV was never below 1bpm. The proportion of tracings without accelerations decreased from 30.1% at 24-25 weeks to 0.5% at 39 weeks. The median number of decelerations was practically zero for all gestational ages. All CTG variables, except decelerations and uterine contractions, showed statistically significant gender differences: baseline was consistently higher in females, while average LTV and average STV tended to be lower in females throughout most of pregnancy. Separate percentile curves were constructed for male and female fetuses. Conclusion: This study provides reference values for CTG parameters throughout pregnancy, derived from the largest dataset of healthy fetuses published to date. For the first time, gender differences were clearly demonstrated in fetal life, and percentile curves constructed separately for male and female fetuses.